Training and Mentoring Correspondence at Sman 1 Sinjai - Erni Ratna Dewi; Mislia; Jamaluddin; Husni BT Salam (www.amertainstitute.com, 2025)
Community service is conducted at SMAN 1 Sinjai to provide assistance in enhancing the understanding of students and staff regarding correspondence. This assistance aims to equip participants with knowledge about how to compose proper letters based on the principles of correspondence. Writing letters correctly is an essential administrative skill that supports effective communication in both academic and professional settings. The main objective of this community service activity is to improve participants' ability to create and compile formal letters correctly while also introducing proper archiving methods. By mastering these skills, participants can enhance their administrative capabilities, which are essential for academic and professional success. This activity is carried out in three main stages: (1) the preparation stage, where materials and lesson plans are structured, (2) the implementation stage, where participants receive direct training and practice writing different types of letters, and (3) the evaluation stage, where the effectiveness of the training is assessed. The results of this community service activity indicate that participants have improved their letter-writing skills, administrative abilities, and overall understanding of effective correspondence. This initiative not only strengthens participants' technical competencies but also prepares them for future academic and professional challenges in administrative and managerial roles.